2023
DOI: 10.3389/fmicb.2023.1017167
|View full text |Cite
|
Sign up to set email alerts
|

Potential of desiccation-tolerant plant growth-promoting rhizobacteria in growth augmentation of wheat (Triticum aestivum L.) under drought stress

Abstract: Wheat (Triticum aestivum L.) yield and physiology are adversely affected due to limited water availability. However, desiccation-tolerant plant growth-promoting rhizobacteria (DT-PGPR) are potential candidates that can overcome the negative impacts of water stress. In the present study, a total of 164 rhizobacterial isolates were screened for desiccation tolerance up to −0.73 MPa osmotic pressure, of which five isolates exhibited growth and expression of plant growth properties under the influence of desiccati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…As functions of symbiosis of mycorrhizal fungi (Chandrasekaran, 2022;Begum et al, 2023;Zou et al, 2023), plant growth-promoting rhizobacteria (PGPR) (Shankar and Prasad, 2023;Tanveer et al, 2023;Zhao et al, 2023), and dark septate endophytes (DSE) (Li et al, 2022;He C. et al, 2022;Liu et al, 2023) during drought stress, root endophytic fungi also play important roles in increasing tolerance to drought stress of their host plants (Azevedo et al, 2021;Manzur et al, 2022;Zuo et al, 2022). S. indica is also a root endophytic fungus, and it improves drought tolerance of their host plants, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…As functions of symbiosis of mycorrhizal fungi (Chandrasekaran, 2022;Begum et al, 2023;Zou et al, 2023), plant growth-promoting rhizobacteria (PGPR) (Shankar and Prasad, 2023;Tanveer et al, 2023;Zhao et al, 2023), and dark septate endophytes (DSE) (Li et al, 2022;He C. et al, 2022;Liu et al, 2023) during drought stress, root endophytic fungi also play important roles in increasing tolerance to drought stress of their host plants (Azevedo et al, 2021;Manzur et al, 2022;Zuo et al, 2022). S. indica is also a root endophytic fungus, and it improves drought tolerance of their host plants, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, rhizobia isolates explored by Kapembwa et al [35] reported that, 88 % had an entire edge, 10 % undulate and 2 % lobate. The rhizobacterial isolates found by Shankar and Prasad [36] had flat, raised, convex, crateriform, or umbonate elevations. In addition, based on the exploration of Odori et al [37], rhizobia colonies that they found appeared mucoid or glistening.…”
Section: Macroscopic Characterizationmentioning
confidence: 93%
“…Also, PGP bacteria increases antioxidant levels, synthesis of ACC deaminase, exopolysaccharides production and ionic homeostasis, which in turn enhances agricultural productivity even in saline-alkaline soil (Mishra et al, 2023). Currently, studies in various parts of the world are reporting improvements in the growth and production of crops such as tomatoes (Fan et al, 2016;Astorga-Elóet al, 2021), maize (Ojuederie and Babalola, 2023), and wheat (Shankar and Prasad, 2023), attribute to the use of PGP bacteria. The utilization of PGP bacteria as inoculants has substantial potential for application in farming, and lowering the rate of chemical fertilizers (Bittencourt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%